Utilizing Group Discussion Technique in Developing Speaking Skill in an EFL Classroom - Kuliahana, Ana; Marzuki, Abdul Gafur (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to identify students’ speaking skills in the English Department at UIN Datokarama Palu that could be developed through group discussion techniques. It was designed as collaborative classroom action research and divided into two cycles. Data came from class observation, field notes, a questionnaire, and a speaking test over six meetings of speaking lessons on the second term of the semester. The research included 22 students. The researcher identified the students’ speaking skill development based on the criteria of success established. The findings showed that 11 students (50%) acquired it, and 11 students (50%) fizzled in the first cycle. The researcher continued to the next cycle since the students’ speaking achievement did not meet the criteria of success yet. Some improvements were made in order to cover the drawbacks in the first cycle, such as rearranging the members of the group and emphasizing teaching on the use of 'opened-ended questions’. There were 18 students (81.8%) who acquired it, and just 4 students (18.2%) fizzled in the second cycle. Besides, all students felt challenged to participate in group discussions. However, their participation varied greatly among the individual students. An interesting implication of this research was that students’ speaking skills could be developed through group discussion techniques.